Freshwater aquaculture in PR China: trends and prospects - Qidong Wang; Lin Cheng; Jiashou Liu; Zhongjie Li; Shouqi Xie; Sena S. De Silva (Wiley Publishing Asia Pty Ltd, 2025)
It is acknowledged that China is the mainstay in global aquaculture, contributing for example, 65.7 (of 76 321 310 t) and 63.6 (of 38 994 913 t) per cent to total global and freshwater aquaculture production, respectively, in 2011, significantly increasing the corresponding contributions from 36.1 and 38.5% of the global total (7 359 881 t) and global freshwater (2 342 706 t) aquaculture production in 1980. Overall, aquaculture production in China in turn has enabled to reduce our dependence on food fish supplies from a hunted to a farmed origin, like all the other staples. However, there are very few accounts on different subsectors of aquaculture in China and even less on variations in aquaculture developments within the country. This review attempts to trace the development trends in inland aquaculture in China in time and space and includes aspects on production, types and modes of culture, species cultured and marketing. It is evident that though inland aquaculture is practised in most provinces of China, the great bulk of it occurs in the area that lies approximately between 110 and 120 °E and 19 and 35 °N, in the Yangtze and Pearl River basins. The review also addresses emerging issues on freshwater aquaculture and possible ways of achieving sustainability in the long term.